Finite element method simulating bursting process of multi-chamber flexible package infusion bag - Yue, Huaijun; Wang, Guanshi; Jiang, Wentao; Tan, Hongbo; Liu, Wenjun; Zhu, Zhongqiang; Zhu, Lin (Sheng wu yi xue gong cheng xue za zhi, 2021)
This study aims to overcome the shortcomings such as low efficiency, high cost and difficult to carry out multi-parameter research, which limited the optimization of infusion bag configuration and manufacture technique by experiment method. We put forward a fluid cavity based finite element method, and it could be used to simulate the stress distribution and deformation process of infusion bag under external load. In this paper, numerical models of infusion bag with different sizes was built, and the fluid-solid coupling deformation process was calculated using the fluid cavity method in software ABAQUS subject to the same boundary conditions with the burst test. The peeling strength which was obtained from the peeling adhesion test was used as failure criterion. The calculated resultant force which makes the computed peeling stress reach the peeling strength was compared with experiment data, and the stress distribution was analyzed compared with the rupture process of burst test. The results showed that con